A large Portuguese corpus on-line: cleaning and preprocessing - Généreux, Michel (2019)
We present a newly available on-line resource for Portuguese,a corpus of 310 million words, a new version of the Reference Corpus of Contemporary Portuguese, now searchable via a user-friendly web interface. Here we report on work carried out on the corpus previous toits publication on-line. We focus on the processes and tools involved for the cleaning, preparation and annotation to make the corpus suitable for linguistic inquiries.